Error Analysis of Indonesian Speaker and Presenter for Practice of Public Speaking Class - Aziz Aziz; Muhammad Darwis; Asriani Abbas (Hasanuddin University, 2022)
This study aimed to reveal the Indonesian language errors found in the DA Public Speaking class. The data collection method used in this research was the observation method. The observation method is collected by recording, listening, and note-taking techniques. Descriptive qualitative method used as the data analysis in this research. The type of data used in this study was divided relating to Indonesian language errors that occur in the DA Public Speaking class. The research results found that participants in the DA Public Speaking class experienced various errors in their appearance in public speaking, either as speakers or presenters. Errors in analysis that often occur are word formation errors, dictions errors, pronunciation errors and sentence formation errors.